2019
DOI: 10.1101/645374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HCMV miR-US22 down-regulation of EGR-1 regulates CD34+ hematopoietic progenitor cell proliferation and viral reactivation

Abstract: JAN) 2 22 45Quiescent stem cells in the bone marrow represent a critical reservoir of latent HCMV, 46 and the mobilization and differentiation of these cells is closely linked to viral reactivation 47 from latency. HCMV encodes small regulatory RNAs, called miRNAs that play important 48 roles in the regulation of viral and cellular gene expression. In this study, we show that 49 HCMV miR-US22 targets Early growth response gene 1 (EGR-1) a host transcription 50 factor that is necessary for stem cell quiescen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Other cmv-miRs have functional roles during latency and reactivation [ 239 ]. While cmv-miR-US22 and cmv-miR-UL22A do not directly exert effects on the MIE enhancer/promoter, they influence HPC proliferation and differentiation [ 240 ], as well as myelosuppression and viral genomic maintenance [ 241 ], respectively.…”
Section: Microrna Regulation Of the Mie Locusmentioning
confidence: 99%
“…Other cmv-miRs have functional roles during latency and reactivation [ 239 ]. While cmv-miR-US22 and cmv-miR-UL22A do not directly exert effects on the MIE enhancer/promoter, they influence HPC proliferation and differentiation [ 240 ], as well as myelosuppression and viral genomic maintenance [ 241 ], respectively.…”
Section: Microrna Regulation Of the Mie Locusmentioning
confidence: 99%
“…It has been predicted that these miRNAs directly regulate the US22 transcript levels, and miR-US22-5p may target autophagy-related 5 (ATG5), a protein associated with autophagy and apoptosis, to modulate apoptosis [76]. Recently, EGR1 has been identified as a target of miR-US22 [41]. EGR1 regulates HCMV gene expression, and the downregulation of the transcription factor mediated by miR-US22 may contribute to the reactivation of HCMV [41,77].…”
Section: Mir-us22mentioning
confidence: 99%
“…Recently, EGR1 has been identified as a target of miR-US22 [41]. EGR1 regulates HCMV gene expression, and the downregulation of the transcription factor mediated by miR-US22 may contribute to the reactivation of HCMV [41,77].…”
Section: Mir-us22mentioning
confidence: 99%
“…MiRNAs are classes of short RNA molecules with 19 to 25 nucleotides, which regarded as one of the regulators of gene expression and silenced target genes in post-transcriptional levels. Growing evidences suggested that miRNAs participate in biological process, for instance, DNA damage response, cell proliferation, cell apoptosis [13][14][15]. With further understanding of biological process, a new regulatory mechanism named competing endogenous RNA (ceRNA) was proposed, which provides a better insight into tumorigenesis [16].…”
Section: Ivyspringmentioning
confidence: 99%